Pengaruh Penambahan Fly Ash dan Serbuk Kaca Terhadap Sifat Fisik dan Mekanik Komposit Batako - Husain, La Ode; Endriatno, Nanang; Aminur, Aminur (Teknik Mesin Universitas Halu Oleo, 2020)
Composite is a new material engineered by two or more materials where the properties of the materials differ from one another both in chemical and physical properties. Composites are obtained from a combination of metal with ceramics, metal with plastics, and others. The purpose of this study was to determine the effect of adding fly ash and glass powder on the physical and mechanical properties of brick-based composites. The drying process is carried out for 28 days. The compressive strength and water absorption tests were carried out after the drying process. The results showed the highest compressive strength value is on the B sample is 74.17 kg / cm2 and water uptake is lowest in the sample A, namely 10.53%. The highest compressive strength test results exist in the sample B is 74.17 kg / cm2 and the compressive strength is lowest in the sample A which is 66.67 kg / cm2. While the highest water absorption test results were in sample C, namely 15.05% and the lowest water absorption value was in sample A, namely 10.53%. Keywords: Brick-Based, fly ash, glass powder, compressive strength, water absorption.